The determination of habitual residence in international marital crises and the importance of its legal substantiation in judicial decisions - García Álvarez, Laura (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
The reason for writing this contribution came as a result of reading a decision from the AP de Santander, on the 4th of May 2022, and the corresponding first instance decision with regards the divorce between two Romanian nationals, temporary workers in Spain. In addition to the incorrect application of EU Regulations (2201/2003 and 2019/1111), the decisions scarcely substantiate the place where the parties were “habitually resident”, an essential point when this determines the access to justice in our domestic courts. In a wider study of other domestic decisions, it has been observed that this type of errors is not infrequent, both in relation to the scope of application of the EU Regulations and of the domestic rules on international jurisdiction, both critically analised, and also to the autonomous concept of “habitual residence” which is present in most of the alternative forums of international jurisdiction concerned.
Keywords: Habitual residence; marital crises; international jurisdiction; 2019/1111 and 2201/2003 EU Regulations; EUCJ case law; residual jurisdiction; domestic rules of international jurisdiction.